Sami Game Jam-Learning, Exploring, Reflecting and Sharing Indigenous Culture through Game Jamming - Kultima, Annakaisa; Laiti, Outi (Digital Games Research Association, 2019)
In this paper, we explore the experiences and lessons learned from Sami Game Jam 2018. Sami Game Jam 2018 was organized in Utsjoki, in a small Sámi village next to the border of Finland and Norway. The group of 44 jammers consisted of local Sámi participants and Finnish as well as international game students and professional developers. The event had 12 Sámi themes to explore that were divided between the teams and the event resulted in six games all combining two. The jam was stressful for the participants and organizers, both Sámi and non-Sámi, but in the end created an invaluable space for rich experiences, learning and self-discoveries. Furthermore, the jam provided a platform for indigenous game development and local game education and a platform to develop Sámi Pedagogy further.